Correlation between high FBXW7 expression in pretreatment biopsy specimens and good response to chemoradiation therapy in patients with locally advanced esophageal cancer: A retrospective study. Issue 1 (11th August 2018) - Gombodorj, Navchaa; Yokobori, Takehiko; Tanaka, Naritaka; Suzuki, Shigemasa; Kuriyama, Kengo; Kumakura, Yuji; Yoshida, Tomonori; Sakai, Makoto; Sohda, Makoto; Baatar, Seded; Miyazaki, Tatsuya; Nishiyama, Masahiko; et al.
Abstract : Background and Objectives: Esophageal squamous cell carcinoma (ESCC) exhibits good reactivity to chemoradiation therapy (CRT). The dysregulation of F‐Box and WD Repeat Domain Containing 7 (FBXW7) is associated with therapeutic resistance in cancer cells. However, the correlation between FBXW7 expression and CRT sensitivity in patients with clinical ESCC has been investigated only in few studies. Therefore, this study aimed to elucidate the significance of FBXW7 expression in pretreatment biopsy specimens from patients with ESCC receiving CRT. Methods: We investigated the relationship between FBXW7 expression and CRT sensitivity in 30 pretreatment biopsy specimens with histological grades of post‐CRT surgically resected tumors. Furthermore, we evaluated the effects of high FBXW7 expression on the sensitivity to cytotoxic agents, including docetaxel and nedaplatin, and radiation in ESCC cells in vitro. Results: High FBXW7 expression before CRT correlated with a good pathological CRT response in patients with advanced ESCC ( P < .05). Further, our in vitro data showed that both chemo and radiation sensitivity increased in TE‐8 and KYSE140 cells overexpressing FBXW7 compared with mock cells because of the degradation of the anti‐apoptotic protein MCL1. Conclusions: The evaluation of FBXW7 expression before CRT treatment is a potential predictor of good responders among patients with ESCC receiving CRT.